2022
DOI: 10.22159/ijap.2022v14i6.43785
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation of Soybean Seeds Using Rhizopus Oligosporus for Tempeh Production and Standardization Based on Isoflavones Content

Abstract: Objective: To determine the best temperature and time of fermentation for making soybean (Glycine max (L.) Merril) tempeh seeds with high content of isoflavones. Methods: Five varieties of soybean seeds, Devon-1, Dena-1, Dega-1, Anjasmoro, and Argomulyo, were determined for their isoflavones content using an Ultraviolet (UV) spectrophotometer. A variety containing the highest isoflavones was washed, boiled, peeled, then mixed with tempeh starter (Rhizopus oligosporus culture) at 1 g/kg. The mixture was then po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…This enzyme could produce isoflavone aglycone resulting from the hydrolysis of isoflavone glycosides. 20 The effect of heat treatment on the enhancement of isoflavone had been reported by Hasanah et al, showing increased genistein from tempeh after boiled, steamed, or fried treatment. This suggested that the continuous hydrolysis process of tempeh through the activation of β-glucosidase enzyme by heat.…”
Section: Effect Of Enzymatic Hydrolysis and Heat Treatment In Daidzei...mentioning
confidence: 85%
“…This enzyme could produce isoflavone aglycone resulting from the hydrolysis of isoflavone glycosides. 20 The effect of heat treatment on the enhancement of isoflavone had been reported by Hasanah et al, showing increased genistein from tempeh after boiled, steamed, or fried treatment. This suggested that the continuous hydrolysis process of tempeh through the activation of β-glucosidase enzyme by heat.…”
Section: Effect Of Enzymatic Hydrolysis and Heat Treatment In Daidzei...mentioning
confidence: 85%
“…In addition, at low temperatures, there is a possibility that bacterial contamination grows faster than the growth rate of Rhizopus sp. (Dwiatmaka et al, 2022). Open access article under the CC BY-NC-SA license be used directly as a source of crude enzyme and easily harvested from the media (Sambo et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The process of making tempeh and cacao tempeh flour was performed according to Dwiatmaka et al (2022) with a slight modification. Tempeh was cut into small pieces and dried in a fluidized bed dryer at 45°C for 4 h. Dry tempeh was then ground using food and sieved using 70 mesh.…”
Section: The Process Of Making Cacao Tempeh Flour and Tekao Flourmentioning
confidence: 99%
“…In seed pre-treatment, steamer duration was longer for cacao beans than for soybean. The antioxidant agents in cacao beans and soybean are mostly contributed by the polyphenol contents of beans, whose compounds are unstable to heat (Indiarto et al, 2019;Oracz & Nebesny, 2016) and reduced during the processing and fermentation process (Dwiatmaka et al, 2022). Cacao bean fermentation by Rhizopus inoculum might not be performed well as the bean is harder than soybean.…”
Section: Particle Size Bulk Density and Angle Of Repose Of Tempeh And...mentioning
confidence: 99%
See 1 more Smart Citation